(3eNJUQ GdLQLGfj aj eUWdM GdMOjKs - (3GdLQLGfj, Ydj Hf eMeO Hf Ydj,, GdeYQha HGdTQja GdLQLGfj J (B816 (3g`s
(3ChdgG (B:s
(3HYO GdHSedI hGdJUdjI (B: (3agPG eNJUQ LGeY deYQaI Yde GdMOjK eQJH Ydi ebOeI hebGUO GdebOeI aj HjGf CUhdg hGUWdGMg GdeJf gh CdaGX GdMOjK GdJj JJbhe HgG GdeYGfj hGdMOjK CYes
(3BNQgG (B:s
(3GdHjgbj hdO SfI CQHY hKdGKeGFI heGJ HfjG HYO KeGf hNeSjf hCQHYeGFI hGdHNGQj hdO jhe GdLeYI dKdGK YTQ NdJ ef ThGd SfI CQHY hJSYjf heGFI heGJ djdI GdaWQ SfI SJ hNeSjf heGFJjfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B5 / 7s
(3eYLe GdeDdajf (B2 / 515s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdMOjK hGdeUWdMs